Correlation of Succinate Metabolism and Virulence in Salmonella typhimurium - Herzberg, Mendel (1965)
Herzberg, Mendel (University of Florida, Gainesville), and Mudhaffer J. Jawad, and Darrell Pratt. Succinate metabolism and virulence in Salmonella typhimurium. J. Bacteriol. 89:185–192. 1965.—A virulent, smooth strain of Salmonella typhimurium (Wild-7) grew slowly with succinate as sole carbon source (Suc-L). Old stock cultures yielded a smooth variant which grew rapidly (Suc-E). Visible colonies of Suc-E appeared in 24 hr, whereas Suc-L required 48 hr. Differences other than the response to succinate were not demonstrable between the two strains; ld(50) values of both strains were similar, but equivalent numbers of Suc-E required longer periods of time to kill mice. Recovery of bacteria from liver and spleen homogenates revealed that Suc-L remains as such in vivo, but Suc-E populations change to Suc-L. By the eighth day of infection, the organisms were 93 to 100% Suc-L; thus, mortality was due to the Suc-L population developed in vivo and not the Suc-E of the original inoculum. Animal passage of a number of stock cultures of S. typhimurium of diverse origin, all Suc-E type, invariably yielded Suc-L. Slow utilization of succinate appears to be correlated with virulence.